History Of Spice Trade And Chinese Brokers In Aceh - Ahmad Fajri; Radiatul Adawiyah (Program Studi Pendidikan Sejarah - Universitas Samudra, 2026)
In the 16th to 18th centuries, the Acehnese spice trade played an important role in the provincial economy. It connects it with international trade routes through the Straits of Malacca. As intermediaries in the spice trade, Chinese brokers play an important role in connecting Aceh with global markets, including China, India, and Europe. This study explores the role of Chinese brokers in the dynamics of the spice trade and how this interaction affects Aceh's position in international trade In this study uses the Historical method, involving the analysis of historical events through a systematic series of actions. It begins by gathering secondary historical sources, including Books and Articles in Journals. After that, source criticism is done to ensure that the information obtained is genuine and credible. The study found that Chinese brokers helped accelerate spice trade routes and strengthen Aceh's economic ties with other countries, strengthening Aceh's position in the global trade network.